AKTUALISASI KURIKULUM MERDEKA PADA MATA PELAJARAN PAI KELAS IV DI SEKOLAH DASAR MUHAMMADIYAH DARUSSALAM GENDENG YOGYAKARTA (DALAM TINJAUAN TAKSONOMI BLOOM) - Nawaf Fauzil Adhim, Hafidz; Nur Hidayat (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine, describe, and analyze the actualization of the Merdeka Curriculum in the PAI (Islamic Education) subject for fourth-grade students at Muhammadiyah Darussalam Gendeng Elementary School, Yogyakarta (in the context of Bloom's Taxonomy). This research employs a qualitative method with a field research type. The research subjects were selected using purposive sampling technique, specifically targeting the fourth-grade PAI teacher at SD Muhammadiyah Darussalam Gendeng Yogyakarta. Data collection techniques included observation, documentation, and interviews. The data analysis used by the researcher involved data reduction, data presentation, and conclusion drawing. The results of this study indicate that the actualization Merdeka Curriculum in the fourth-grade PAI subject, viewed through Bloom's Taxonomy theory, shows that the material meets the needs of students based on cognitive, affective, and psychomotor domains. The Merdeka Curriculum, as an essential aspect in achieving educational goals, aims to enhance students' interests and talents and stimulate the development of their morals/character.